2011
DOI: 10.1021/nl2038216
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Structure and Structural Stability of Sc75Fe25 Nanoglasses

Abstract: Nanoglasses are solids consisting of nanometer-sized glassy regions connected by interfaces having a reduced density. We studied the structure of Sc(75)Fe(25) nanoglasses by electron microscopy, positron annihilation spectroscopy, and small-/wide-angle X-ray scattering. The positron annihilation spectroscopy measurements showed that the as-prepared nanoglasses consisted of 65 vol% glassy and 35 vol% interfacial regions. By applying temperature annealing to the nanoglasses and measuring in situ small-angle X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
100
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(107 citation statements)
references
References 17 publications
7
100
0
Order By: Relevance
“…Consequently, the NG exhibits a more homogeneous plastic deformation carried by a pattern of multiple shear bands [12] as compared to the bulk metallic glass (BMG), where plastic deformation is well localized in a few dominant shear bands. The influence of interfaces on the deformation behavior of nanoglasses has been shown both in computer simulation [11,13,14] and experiment [9,15], where also an enhanced plasticity under compression was observed indicating that not critical shear bands occur. Recent experiments on sputtered nanograined Au-based glasses also showed high hardness and a low elastic modulus as compared to their bulk counterparts [8].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Consequently, the NG exhibits a more homogeneous plastic deformation carried by a pattern of multiple shear bands [12] as compared to the bulk metallic glass (BMG), where plastic deformation is well localized in a few dominant shear bands. The influence of interfaces on the deformation behavior of nanoglasses has been shown both in computer simulation [11,13,14] and experiment [9,15], where also an enhanced plasticity under compression was observed indicating that not critical shear bands occur. Recent experiments on sputtered nanograined Au-based glasses also showed high hardness and a low elastic modulus as compared to their bulk counterparts [8].…”
Section: Introductionmentioning
confidence: 92%
“…The recent work of Chen et al [8], supports Gleiter's results on the structural model of a NG. The microstructure of a metallic nanoglass consisting of glassy grains and glass-glass interfaces has been experimentally revealed by electron microscopy, small-angle X-ray scattering and positron annihilation spectroscopy [9], while molecular dynamics studies showed that glass-glass interfaces exhibit an excess free volume and a modified local order [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…as in nanoglasses. The desire to explain their unusual structures and properties [15][16] [17] requires improved characterization methods.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of reduction in atomic density of amorphous materials when the particle size is reduced to nano-range was first discovered by Gleiter [23]. Classical molecular dynamics simulations on Cu-Ti [23] and CuZr [24] amorphous systems and experimental measurements in other systems like Sc-Fe [25] have revealed that the lowering in atomic density is due to diffusion of free volume from interfaces formed between glassy nano-particles.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%